Economic efficiency of mergers in the Czech Republic 2001–2010 - Sedláček, Jaroslav; Valouch, Petr; Králová, Maria (Technological and Economic Development of Economy, 2014)
The paper presents partial results of research focusing on accounting, taxation and legal aspects of mergers in the Czech market. The input source is a database of mergers implemented in the Czech territory, which compiles data taken from the Trade Register for the decade of 2001–2010. The structure of the data allows for an evaluation of development trends of mergers in the Czech market, analysis of economic consequences of mergers and finding possible causes of their success or failure. From economic characteristics of merger success, we have chosen the item of net assets. Statistical testing of the hypothesis proved that mergers do not affect net assets during the period of three years after the merger implementation. A significant dependence of net assets development on mergers was proved after the basic set was stratified based on the size of companies. Mergers have a positive effect on the growth of value for owners in the group of small enterprises in the third year after the merger; the value in the group of medium enterprises also grows, but not significantly. Regarding large enterprises, the net assets even decreased in consequence of a merger.